182k views
4 votes
For f (x) = 3x +1 and g(x) = x^2-6, find (g/f)(x)

1 Answer

3 votes

Answer:


(g/f) (x) =(x^2-6)/(3x+1)

Explanation:

We have the following functions


f (x) = 3x+1


g (x) = x^2-6

To find
(g/f)(x) we must divide the function g(x) with the function f(x)

Then we perform the following operation


(g/f) (x) =(x^2-6)/(3x+1)

Finally we have that:


(g/f) (x) =(x^2-6)/(3x+1)

For
x \\eq -(1)/(3)

User PetersenDidIt
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.